Infection after Acute Ischemic Stroke: Risk Factors, Biomarkers, and Outcome - Katja E. Wartenberg; Anett Stoll; Andreas Funk; Andreas Meyer; J. Michael Schmidt; Joerg Berrouschot (Stroke Research and Treatment)
Background. The activation of inflammatory cascades triggered by ischemic stroke may play a key role in the development of infections. Methods. Patients admitted with ischemic stroke within 24 hours were prospectively enrolled. Biomarkers of infection were measured on days 1, 3, and 5. The patients were continuously monitored for predefined infections. Results. Patients with infection were older (OR 1.06 per year, 95% CI 1.01–1.11) and had a higher National Institute of Health Stroke Scale Score (NIHSS, OR 1.21, 95% CI 1.10–1.34), localization in the insula, and higher stroke volumes on diffusion-weighted imaging. The maximum temperature on days 1 and 3, leukocytes, interleukin-6, lipopolysaccharide-binding protein on days 1, 3, and 5, C-reactive protein on days 3 and 5, and procalcitonin on day 5 were higher and HLA-DR-expression on monocytes on days 1, 3, and 5 lower in patients with infection. Age and NIHSS predicted the development of infections. Infection was an independent predictor of poor functional outcome. Conclusions. Severe stroke and increasing age were shown to be early predictors for infections after stroke.